(9u+2)(6u+1)=0

Simple and best practice solution for (9u+2)(6u+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9u+2)(6u+1)=0 equation:


Simplifying
(9u + 2)(6u + 1) = 0

Reorder the terms:
(2 + 9u)(6u + 1) = 0

Reorder the terms:
(2 + 9u)(1 + 6u) = 0

Multiply (2 + 9u) * (1 + 6u)
(2(1 + 6u) + 9u * (1 + 6u)) = 0
((1 * 2 + 6u * 2) + 9u * (1 + 6u)) = 0
((2 + 12u) + 9u * (1 + 6u)) = 0
(2 + 12u + (1 * 9u + 6u * 9u)) = 0
(2 + 12u + (9u + 54u2)) = 0

Combine like terms: 12u + 9u = 21u
(2 + 21u + 54u2) = 0

Solving
2 + 21u + 54u2 = 0

Solving for variable 'u'.

Factor a trinomial.
(2 + 9u)(1 + 6u) = 0

Subproblem 1

Set the factor '(2 + 9u)' equal to zero and attempt to solve: Simplifying 2 + 9u = 0 Solving 2 + 9u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 9u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 9u = 0 + -2 9u = 0 + -2 Combine like terms: 0 + -2 = -2 9u = -2 Divide each side by '9'. u = -0.2222222222 Simplifying u = -0.2222222222

Subproblem 2

Set the factor '(1 + 6u)' equal to zero and attempt to solve: Simplifying 1 + 6u = 0 Solving 1 + 6u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 6u = 0 + -1 6u = 0 + -1 Combine like terms: 0 + -1 = -1 6u = -1 Divide each side by '6'. u = -0.1666666667 Simplifying u = -0.1666666667

Solution

u = {-0.2222222222, -0.1666666667}

See similar equations:

| 20x=240+12x-360 | | (T-7)(6t-7)=0 | | -6(1+r)-8r=92 | | 2(3x+4)=5(x-1)+x+13 | | 2x+9=2x+22 | | J=z-a/x | | 5t+4=1t-2 | | J(8j-7)=0 | | -3x+-6= | | 6(2a+10)=5a+5 | | 21-2x=43-5x | | 6d-2= | | (x)/(2)-1=2-x | | ×/3=11 | | (-4.3)-z=11 | | 2x+2=4+6x-54 | | 47-7x=5x-20 | | (S+5)(8s+9)=0 | | 7.9x-17.9=29.5 | | -12(x+4)=-3(x+6)+x-30 | | 0.5(4x-1)=4(3+x) | | 2a+28=4a-4 | | 144-5x=171-8x | | 3(x+3)-10=32 | | 6x+5+3x=136 | | 12-x=36 | | (7n-3)(6n-7)=0 | | h=(-16)t^2+800(t)+125 | | sin(5t)-cos(5t)=0 | | 6a-5= | | (8z-1)(z+3)=0 | | 130x+46=7 |

Equations solver categories